Tyrosinase Inhibitor and Antioxidant Activity of Seaweed Powder from Fresh and Dried Sargassum plagyophyllum - Ayun Erwina Arifianti; Effionora Anwar; Nurjanah Nurjanah (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
Sargassum plagyophyllum from Sargassaceae family contains various bioactive compounds, namelyphlorotannin which is reported as an antioxidant and tyrosinase inhibitor. Tyrosinase inhibitor andantioxidant activity from seaweed powder that obtained from seaweed’s slurry have not been reported.Thus, this study was aimed to obtain the best seaweed slurry and powder from Sargassum plagyophyllumbased on tyrosinase inhibitor and antioxidant activity, so it can be used as active substance in skinlightening cosmetic formula. Sargassum plagyophyllum which prepared fresh and dried was processedinto seaweed slurry and lyophilization to form powder. Antioxidant activity which was determined by2,2-Diphenyl-1-picrylhydrazyl (DPPH) radical scavenging method found the IC50 values of ascorbic acidwas 0.0035 mg/mL; fresh slurry 27.31 mg/mL; dried slurry 41.13 mg/mL; fresh powder 2.21 mg/mL; anddried powder 13.18 mg/mL. Moreover, the tyrosinase inhibitory activity which was measured by enzimaticreaction with L-tyrosine as substrate found IC50 values kojic acid 0.0076 mg/mL; fresh powder 4.97 mg/mL;and dried powder 11.35 mg/mL. Seaweed powder obtained from fresh ingredient is the most optimal resultbased on its tyrosinase inhibitor and antioxidant activity, thus potential to be developed further as activesubstance for lightening cosmetic formula.